Brazilian cuisine and the bustling gourmet universe - Arruda , Luzia da Silva (Seven Editora, 2023)
When one thinks of Brazilian cuisine, what immediately comes to mind is the triad of influences: indigenous, African and Portuguese present in classic works of national gastronomic literature, such as that of Luís da Câmara Cascudo and Gilberto Freyre. There is no denying that we are the fruits of a miscegenation, in fact Martín-Barbero (2002, p.50) points out: "the history of Latin America is the history of miscegenation and not the history of purities, of authenticities, whether we like it or not". DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-075